Enhancing Climate Resilience and Productivity in Cambodia by Improving Rice-Field Fisheries - Sean, Vichet (WorldFish, 2025)
This poster presents an innovative, science-driven approach integrating rice and fisheries to enhance climate resilience and rural livelihoods in Cambodia. Through improved rice-field fisheries (RFF) management and Community Fish Refuges (CFRs), the approach boosts food security, income, and adaptive capacity. Supported by CGIAR’s Scaling for Impact and national partners, the model is expanding across key regions. Results show strong gains: up to 97 kg of fish, 27 kg of OAA, and 4 kg of aquatic plants per hectare per year. Over 160 CFRs near Tonle Sap directly benefit 500,000 people. While more than 900 CFRs serve 2 million people, many need better management. More than 40 resilient fish species have been recorded, reinforcing the system’s climate adaptation potential.